THE DEPTH OF THE SPINEL TO GARNET TRANSITION AT THE PERIDOTITE SOLIDUS - Robinson J.A.C.; Wood B.J. (My University, 1998)
We have determined the pressure and temperature of the spinel-garnet transition close to the solidus of fertile and depleted peridotite from a combination of synthesis, sandwich and garnet-seeded experiments. Garnet is unstable in MORB-Pyrolite below 2.8 GPa (depths <85 km) at a solidus temperature of 1470°C. In Tinaquillo Lherzolite, which is related to MORB-Pyrolite by about 7% fractional melting, the transformation occurs at 3.1 GPa at a solidus temperature of 1520°C. In both cases the transformation interval is narrow, approximately 0.1-0.2 GPa. Because the solidus temperature increases by 7°C and the spinel-garnet transformation pressure by 0.05 GPa for every 1% melt extracted, extremely high potential temperatures (Tp > 1450°C) are required to generate the 3-5% melting in the garnet field implied by recent trace element and isotope studies. It appears likely, therefore, that the `garnet signature' arises from some mechanism other than anhydrous melting of garnet peridotite.
Keywords: PERIDOTITES; SPINEL; GARNET GROUP; LHERZOLITE; PYROLITE